Вы находитесь на странице: 1из 26

Roots of

Polynomial
s

To find the roots of

polynomial equations of
the general form:
fn(x) = a0 + a1x + a2x2 + +anxn

Where n = the order of the polynomial

and the as = constant coefficients.
Although the coefficients can be complex
numbers, we will limit our discussion to
cases where they are real. For such
cases, the roots can be real and/or
complex.

The roots of such polynomials

1. For an nth-order equation, there are n real or
complex roots. It should be noted that these
roots will not necessarily be distinct.
2. If n is odd, there is at least one real root.
3. If complex roots exist, they exist in conjugate
pairs (that is, + i and i), where i = 1.

Mullers
Method

Mllers method takes a similar approach, but

projects a parabola through three points.
The method consists of deriving the coefficients
of the parabola that goes through the three
points. These coefficients can then be substituted
into the quadratic formula to obtain the point
where the parabola intercepts the x axisthat is,
the root estimate. The approach is facilitated by
writing the parabolic equation in a convenient
form,

The coefficients of equation above can be

evaluated by substituting each of the three points
to give
f(x0) = a(x0 x2)2 + b(x0 x2) + c
f(x1) = a(x1 x2)2 + b(x1 x2) + c
f(x2) = a(x2 x2)2 + b(x2 x2) + c

Because we have three equations, we can solve

for the three unknown coefficients, a, b, and c.

c = f (x2)
f(x0) f(x2) = a(x0 x2)2 + b(x0 x2)
f(x1) f(x2) = a(x1 x2)2 + b(x1 x2)

Algebraic manipulation can then be used to

solve for the remaining coefficients, a and b.
One way to do this involves defining a number
of differences,

h0 = x1 x0

h1 = x2 x1

f(x1)-f(x0)
0 =
x1-x0
1 =f(x2)-f(x1)
x2-x1

Which can be solved for a, b and c. The results

can be summarized as :

1 0
a=
x1-x0
b= ah1 + 1
c= f(x2)

To find the root, we apply the quadratic

formula. However, because of potential roundoff error, rather than using the conventional
form, we use the alternative formulation

x3 = x 2 +

-2c
bb2-4ac

Note that the use of the quadratic formula

means that both real and complex roots can be
located. This is a major benefit of the method.
the error can be calculated as:
x3 - x2

Ea =

x3

X 100 %

Once x3 is determined, the process is repeated.

This brings up the issue of which point is
discarded. Two general strategies are typically
used:
1. If only real roots are being located, we choose
the two original points that are nearest the new
root estimate, x3.
2. If both real and complex roots are being
evaluated, a sequential approach is employed.
That is, just like the secant method, x1, x2, and
x3 take the place of x0, x1, and x2.

Bairstows Method

Bairstows method is an iterative approach related

loosely to both the Mller and Newton- Raphson
methods. Before launching into a mathematical
description of the technique, recall the factored
form of the polynomial,

Can be divided by the factor x t to yield a second

polynomial that is one order lower,
fn1(x) = b1 + b2x ++b3xn2+bnxn1
with a remainder R = b0, where the coefficients can
be calculated by the recurrence relationship
bn = an
bi = ai + bi+1t
for i = n 1 to 0
Note that if t were a root of the original polynomial,
the remainder b0 would equal zero.

To permit the evaluation of complex roots,

Bairstows method divides the polynomial by a
quadratic factor x2 rx s. The result is a new
polynomial
fn2(x) = b2 + b3x ++bn-1xn-3 + bnxn2

with a remainder:
R = b1(x r ) + b0

As with normal synthetic division, a simple

recurrence relationship can be used to perform the
bn = an
bn1 = an1 + rbn
bi = ai + rbi+1 + sbi+2

for i = n 2 to 0

If x2 rx s is an exact divisor of the

polynomial, complex roots can be determined by
Thus, the method reduces to determining the
values of r and s that make the quadratic factor an
exact divisor. In other words, we seek the values
that make the remainder term equal to zero.

Bairstows method uses a strategy similar to the

Newton- Raphson approach. Because both b0 and
b1 are functions of both r and s, they can be
expanded using a Taylor series
b1
b1
b1(r + r,s + s) = b1 +
r +
s
r
s
b0
b0
b0(r + r,s + s) = b0 +
r +
s
r
s
where the values on the right-hand side are all
evaluated at r and s

The changes, r and s , needed to improve our

guesses can be estimated by setting equal to
zero to give
b1
r
b0
r

r +
r +

b1
r
b0
r

s = - b1
s = - b0

If the partial derivatives of the bs can be

determined, these are a system of two equations
that can be solved simultaneously for the two
unknowns, r and s.
Bairstow showed that the partial derivatives can
be obtained by a synthetic division of the bs in a
fashion similar to the way in which the bs
themselves were derived:
cn = bn
cn1 = bn1 + rcn
ci = bi + rci+1 + sci+2

for i = n 2 to 1

Where:
b0
r
b0
s
b1

= c1

b1

= c2

r
= c3

Thus,sthe partial derivatives are obtained by

synthetic division of the bs.

Then the partial derivatives can be substituted

and yield
c2 r + c3 s = b1
c1 r + c2 s = b0
These equations can be solved for r and s,
which can in turn be employed to improve the
initial guesses of r and s.

At each step, an approximate error in r and s can

be estimated, as in

r X 100 %
s
= s X 100 %

Ea,r
Ea,s

When both of these error estimates fall below a

prespecified stopping criterion s, the values of
the roots can be determined by
x=

r r2+4s
2

At this point, three possibilities exist:

1. The quotient is a third-order polynomial or greater. For
this case, Bairstows method would be applied to the
quotient to evaluate new values for r and s. The previous
values of r and s can serve as the starting guesses for this
application.
2. The quotient is a quadratic.
3. The quotient is a first-order polynomial. For this case,
the remaining single root can be evaluated simply as
x=

S
r